Audiology and Hearing Health in Islamabad and Rawalpindi: Awareness Perspective: Audiology and Hearing Health - Saqulain, Ghulam; Pervaiz, Asma; Qazafi, Laiba; Zahid, Khadija; Sami, Muhammad Abdul (Pakistan BioMedical Journal, 2024)
There exists a literature gap on public awareness of audiologists and their services in Pakistan. The educated population’s awareness is of utmost concern as they are a knowledge resource for the masses especially the uneducated with low literacy. Objective: To assess the impact of public awareness on audiology and hearing health in Islamabad and Rawalpindi. Methods: This cross-sectional study was performed at Shifa International Hospital from February to June 2023. n= 377 participants were recruited using random sampling and assessed using a 15-item closed-ended questionnaire. Results: Regarding knowledge of the profession of audiology, (92.8%) never visited an audiologist and (58.1%) heard about an audiologist by word of mouth. (45.6%) considered important to get their hearing tested and (61.8%) thought that the hearing of adults can be tested. (34.2%) thought that ear infection causes hearing difficulties followed by noise (33.2%). Despite (97%) recognizing the importance of hearing tests, only (7.2%) consulted an audiologist. They had knowledge that ear infection and loud noise could lead to hearing loss and believed in keeping their ears clean with cotton buds. Conclusions: It was concluded the study reveals a lack of awareness regarding audiology as a profession, leading to a limited number of individuals seeking audiological services. While there is a general understanding of the importance of hearing testing and recognition of the causes of hearing loss, there is room for improvement in raising awareness about the specialized role of audiologists in addressing hearing-related issues.